T-cell/Histiocyte-rich Large B-cell Lymphoma in an Adolescent from Abidjan-Ivory Coast: Case Report - Ismael Kamara; Kodzovi Mawulé Corcellar Womey; Dohoma A. Silué; Réné-Paule Botti; Ruth Djeke; Boidy Kouakou; Gustave Koffi (European Scientific Journal, ESJ, 2023)
T-cell/Histiocyte-rich large B-cell lymphoma (THRLBCL) is a rare pathology, uncommon in the children population, and the few cases reported had a wide range of clinical presentations, including advanced stage, extranodal involvement, and bad prognosis. The authors report a case of a 16-year-old male patient with no medical history, who presented a single left axillary adenopathy. T-cell/Histiocyte-rich large B-cell lymphoma was diagnosed by immunohistochemistry and was classified good prognosis. RCHOP-based chemotherapy was performed with good progress. The authors hope to contribute to the literature on THRLBCL and draw the attention of practitioners to its occurrence in the pediatric population.